The effect of ultrasound on improving the extraction of tannins from the Stryphnodendron adstringens bark - de Souza Ribeiro, Maurício M.; Viganó, Juliane; de Novais, Nathália Stahl; de Souza Mesquita, Leonardo M.; Kamikawachi, Renan Canute [UNESP]; Vilegas, Wagner [UNESP]; Lopes, Patricia Santos; Soares da Silva, Camila; Rostagno, Maurício Ariel; Veggi, Priscila Carvalho (Elsevier, 2023)
Stryphnodendron adstringens (Barbatimão) barks is one of the plants listed in the national list of medicinal plants of interest to the Brazilian health system and in the Brazilian pharmacopeia. Its extracts have been used in commercial products and popular medicine due to their phenolic compound's composition. Reported works dealing with Barbatimão and ultrasound-assisted extraction (UAE) does not cover all possible variables to be studied. Also, there is a gap in understanding the ultrasound phenomena's effect on the extract composition and biological properties of the Barbatimão. This work aimed to apply the UAE, using hydroethanolic solution (50 wt%) as the solvent to recover phenolic compounds from Barbatimão barks. Amplitude (0–40%), solvent-to-feed mass ratio (5-25), and extraction time (2–12 min) were evaluated. Ferric-reducing antioxidant capacity (FRAP), antioxidant cell activity, and cytotoxicity were also evaluated. The results showed that UAE parameters play significant roles in obtaining higher yields of phenolic compounds compared to other processes including conventional techniques. It was identified that the ultrasound waves contribute to enhancing the tannin extraction through mechanisms that only ultrasound, among the tested techniques, can provide. The extract obtained by UAE promoted cell viability higher than 80%, while the extracts obtained by the conventional method did not demonstrate this activity. UAE showed an efficient technique to obtain a tannins-rich extract from Barbatimãobarks.
Keywords: Antioxidant activity; Flavonoids; Green extraction; Medicinal plant; Phenolic compounds; Tannins